Benefits of Studying Abroad for Graduate Employability: Perspectives of Exchange Students From Lao Universities - Sisavath, Soubin (Journal of International Students, 2021)
This study investigated the benefits of studying abroad with student exchange programs for graduate employability. Data were drawn from a survey with 163 Lao former exchange participants at three public universities in Laos, followed by 19 semi-structured interviews. Results revealed that participants benefited from participating in overseas exchanges at a high level in terms of the development of employability skills, particularly interpersonal and communication skills, and in multidisciplinary knowledge and international competences. Study abroad experience was positively considered as being related to increasing job opportunities, which signal better educational credentials with proven skills that are demanded in the domestic labor market. This study offers useful insights into the benefits of student exchange programs and adds perspectives from a developing country whose voice has been little heard in the literature on the value of study abroad.